Review paper Penile premalignant lesions: terminology, classification and risk of malignant transformation - Michajłowski, Igor; Sobjanek, Michał; Michajłowski, Jerzy; Włodarkiewicz, Adam; Biernat, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Over 95% of all malignant tumors of the penis represent squamous cell carcinoma. A significant proportion of these tumors develop on the basis of precancerous lesions, others appear in clinically unchanged mucosa. Early detection and treatment of lesions with a risk of malignant transformation can prevent the development of invasion. In this paper we present the terminology, available classifications and the risk of malignant transformation of precancerous lesions of the penis.